Increasing Work Productivity by Building a Work Culture and Preventive Discipline Study at a Construction Consulting Company in Bandung City - Firmansyah Damanik (Majalah Bisnis & IPTEK, 2026)
This study aims to investigate the effects of organizational culture and preventive discipline on employee productivity within the construction consulting sector. Utilizing a survey approach, data was collected from 47 employees to analyze the relationships among these variables using Partial Least Squares Structural Equation Modeling (PLS SEM). The results indicate that organizational culture significantly influences both preventive discipline and productivity, with strong path values of 0.850 for preventive discipline and 0.314 for productivity. Preventive discipline also demonstrates a significant positive effect on productivity, with a path value of 0.628. The model explains 72.2% of the variance in preventive discipline and 82.9% in productivity. These findings imply that fostering a positive organizational culture and implementing effective preventive discipline can substantially enhance employee productivity. Organizations in the construction consulting sector can benefit from these insights by prioritizing cultural initiatives and discipline policies to optimize performance.